2019
DOI: 10.3390/su11061673
|View full text |Cite
|
Sign up to set email alerts
|

Executive Compensation, Sustainability, Climate, Environmental Concerns, and Company Financial Performance: Evidence from Indonesian Commercial Banks

Abstract: This research investigates whether executive compensation is designed to motivate managers to pursue corporate sustainability (CS) concerns as measured by Global Reporting Initiative (GRI) 3.1 disclosure indicators in Indonesian listed commercial banks throughout 2007–2014. In addition, this study examines the impact of executive compensation, climate, and environmental concerns on both financial health and market value performance as components of company financial performance (CFP). This study, based on an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(95 citation statements)
references
References 85 publications
8
84
1
2
Order By: Relevance
“…When we add the sizes of banks to our model, the environment and human resources have still a significant and negative effect on ROA. These results show a parallelism with the study of Kartadjumena and Rodgers (2019) in which the effect of sustainability performance on banks' financial performance was analyzed in India. This also shows that the workouts of banks on environment and human resources are just a cost object for most of the shareholders.…”
Section: Discussion and Recommendationssupporting
confidence: 79%
See 2 more Smart Citations
“…When we add the sizes of banks to our model, the environment and human resources have still a significant and negative effect on ROA. These results show a parallelism with the study of Kartadjumena and Rodgers (2019) in which the effect of sustainability performance on banks' financial performance was analyzed in India. This also shows that the workouts of banks on environment and human resources are just a cost object for most of the shareholders.…”
Section: Discussion and Recommendationssupporting
confidence: 79%
“…According to the table, we see that Multi-Criteria Decision-Making Models and statistical comparison methods were used to compare banks, on the other hand; panel data analysis was used to find out the effect of relations between sustainability and banks. When we check the studies in which panel data analysis was used to find out relations between sustainability performance and financial performance, we see that Buallay [6] found a positive relationship in general, Matuszak & Rózanska [21] couldn't find a relationship in general and Kartadjumena & Rodgers [16] found a negative relationship in general. As you see, these studies couldn't find a common relationship between sustainability performance and financial performance in the banking sector.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A safe and sound banking system aids a nation in its economic development by channeling money from fund providers to users [33,34]. Kartadjumena and Rodgers [35] found that when corporate executives become more conscious of sustainability, they strive to improve company financial performance (CFP). For this reason, FSC, the regulatory authority for financial institutions, supervise banks so that banks adhere to their fundamental values of helping individuals and businesses to access the needed funds in fulfillment of their personal and business goals, thus stimulating the wealth and prosperity of the community as a whole [5].…”
Section: Linkage Between Sustainability and Financial Performance In mentioning
confidence: 99%
“…Therefore, it is expected that the decisions of the organization are consistent with gender diversity trends. As Kartadjumena and Rodgers [106] argue, companies can improve their management decisions when the interests of different stakeholders are taken into account, in addition to shareholders.…”
Section: Reconciliation Of Work and Family Lifementioning
confidence: 99%